The financial crisis: A wake-up call for strengthening regional monitoring of financial markets and regional coordination of financial sector policies? - Adalbert Winkler (Asian Development Bank Institute (ADBI), 2010)
How much can regional monitoring of financial markets and coordination of financial sector policies contribute to preventing and mitigating financial crises? This paper reviews and compares the experiences of Europe and Asia, which have taken different routes and have achieved different levels of regional financial integration. The analysis suggests that the harmonization and coordination of regulation and supervision, with a strong focus on maturity and currency mismatch problems, would constitute an important step toward mitigating the risk of crisis. However, regional monitoring and coordination will remain difficult as long as lender-of-last-resort activities and fiscal support packages are organized on a national level. Against this background, the crisis is a wake-up call for further progress on monetary integration in Asia along the lines of the reformed Chiang Mai Initiative. In Europe, the crisis reveals the need to establish a sustainable regulatory and supervisory structure that properly defines and reflects the responsibilities of regional and national authorities in crisis management, including its fiscal dimension.
Keywords: F15; F33; F36; G38; 330; Kapitalmarktliberalisierung; Internationale wirtschaftspolitische Koordination; Finanzmarktkrise; Asien